ROLE OF RELIGIOUS ELEMENTS IN PAKISTAN MOVEMENT: ROLE OF RELIGIOUS ELEMENTS IN PAKISTAN MOVEMENT - Dr. Muhammad Rizwan; Syed Usman Ali Shah Kazmi (International Research Journal of Arabic and Islamic Studies, 2022)
Religious elements have played a tremendous role to strive for independence, however, if one faction of the Ulema supported the movement under Jinnah’s leadership, the others, at this occasion, bitterly opposed the creation of a separate state by propagating the Indian Nationalism. Yet there is a long list of Ulema from different religious parties who laid their lives in the struggle for freedom. Fight for the cause of Pakistan has not been started in early 1930s but the Muslims of subcontinent tried their best to get rid of the British dominancy since the establishment of colonial rule. Current study will strive to analyze the role of Ulema finally paved the way for an independent Muslim state. It will try to pin point that how their freedom struggle remained an un-separable like the two sides of a coin representing a single worth. Descriptive method have been used with most of the secondary sources including books, journal, internet, writings of international scholars published materials and newspaper for the collection and evaluating data. It is an attempt to get the answer that how Ulema from different sectors, along with other elements, successfully ended the British rule in the subcontinent.